Cerebrospinal fluid immunological biomarkers associated with axonal damage in multiple sclerosis. (17th October 2014) - Villar, L. M.; Picón, C.; Costa‐Frossard, L.; Alenda, R.; García‐Caldentey, J.; Espiño, M.; Muriel, A.; Álvarez‐Cermeño, J. C.
<x xml:space="preserve">Abstract</x> Background and purpose Cerebrospinal fluid (CSF) neurofilament light protein (NFL) is a promising biomarker of axonal injury and neurodegeneration. Here CSF lymphocyte subpopulations and antibodies, potential players of neurodegeneration, are examined in relation to CSF NFL shedding in MS. Methods Cerebrospinal fluid NFL from 127 consecutive untreated MS patients was analysed. Samples from 37 age‐matched patients with other central nervous system non‐inflammatory neurological diseases (NIND) were also assessed. CD4+, CD8+, CD56+ and CD19+ cell subsets were studied by flow cytometry. Oligoclonal IgG and IgM bands (OCMB) against lipids were studied by isoelectric focusing and immunoblotting. These data were analysed in relation to clinical and magnetic resonance imaging features. Results A CSF NFL cut‐off value of 900 ng/l (mean + 3 SD of NIND values) was calculated. MS patients with increased NFL values showed significantly higher Multiple Sclerosis Severity Score and magnetic resonance imaging lesion number. The presence of OCMB (P < 0.0001) and elevated T and B lymphocyte counts was associated with increased levels of CSF NFL. Conclusions High CSF NFL levels are associated with elevated CSF lymphocyte cell counts and intrathecal synthesis of IgM against lipids. These findings support a role for OCMB in the axonal damage of MS offering a rationale for the association of these antibodies with disability and brain atrophy progression in MS.